Assessment of Nurses’ Knowledge Regarding Personal Protective Equipment at Two Tertiary Care Hospitals, Peshawar : Nurses’ Knowledge Regarding Personal Protective Equipment - Nazar, Gul; Ahmad, Imran Waheed; Muhammad, Dildar (Pakistan Journal of Health Sciences, 2023)
Personal Protective Equipment (PPE) include gloves, protective eye wear (goggles), mask, respirator, apron, gown, boots/shoe cover, hair cover and are aimed to shield Health Care Professionals (HCP) including nurses from workplace infections and injuries. Objective: To assess nurses’ knowledge regarding personal protective equipment at two tertiary care hospitals in Peshawar. Methods: A design of the study was descriptive cross-sectional survey. Overall, 150 nurses were involved by using consecutive sampling technique. Data were collected through structured, self-administered adopted questionnaire. Results: This study comprised of 150 contributors including 30% male and 70% female. The mean age of the participants was 29.15 with standard deviation ± 6.07. 53.3% of the participants had Diploma, 36.7% had Post RN, 8.7% of the participants had BSN and 1.3% of the participants had MSN degrees. The study showed that 58% of respondents had good knowledge due to their professional experiences while 36% had average knowledge level due to low professional experiences and lack of resource and availability of PPE’s and only 6% participants had poor knowledge level regarding personal protective equipment due to lack of professional experiences. Conclusions: This study concluded that knowledge level was good in majority of nurses. Despite the good knowledge level, some of the personnel practices and attitudes towards PPE remain unchanged. This study pleas for a need to educate Nurses on PPE; it may be with continuing education on infection control or other informative platforms. When there is low level of knowledge it will affect practice related to PPE.